2017
DOI: 10.18203/2394-6040.ijcmph20175322
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of neonatal deaths in Maharashtra: policy implications

Abstract: Background: As per statistics on infant mortality, the State of Maharashtra has done well in bringing down IMR from 33 to 21 per 1000 live births. However a lot needs to be achieved still. Various child health programs like home based new born care and others have improved child survival. But the analysis of cases will throw light on actionable points for policy change. Methods: Keeping in mind mortality statistics of the State, an analysis was done on causes of neonatal deaths and social determinants. A retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Though the majority of 0–2-day deaths occurred at the facility irrespective of the type of health facility, the proportion of public sector births dying at the facility was significantly lower than the private sector births for 3–27-day deaths. Also, as the mean days of stay were significantly lower in the former than the latter, further in-depth exploration would be useful to understand the context of duration of facility stay in relation to the delivery complications or other barriers such as costs and quality of care in addition to the treatment-seeking behaviour to develop strategies to reduce neonatal mortality [59].…”
Section: Discussionmentioning
confidence: 99%
“…Though the majority of 0–2-day deaths occurred at the facility irrespective of the type of health facility, the proportion of public sector births dying at the facility was significantly lower than the private sector births for 3–27-day deaths. Also, as the mean days of stay were significantly lower in the former than the latter, further in-depth exploration would be useful to understand the context of duration of facility stay in relation to the delivery complications or other barriers such as costs and quality of care in addition to the treatment-seeking behaviour to develop strategies to reduce neonatal mortality [59].…”
Section: Discussionmentioning
confidence: 99%
“…Few authors have pointed out the fact that these in-hospital delays (level II delays) in provision of healthcare to neonates amount to significant morbidity and contributed to as much as 40.8% of neonatal deaths. 12 WHO data has shown that these anomalies (birth defects) contribute to 8.1% of neonatal deaths. Severe forms of congenital anomalies present during neonatal period and need early surgical correction; otherwise leading to death of the affected newborn.…”
Section: Discussionmentioning
confidence: 99%
“…The risks experienced by Madia-Gond women starts from birth itself, with preterm births and low-birth weight babies during delivery being a prevalent phenomenon. Bhamaragadh’s neonatal mortality is high, accounting for 12.4% of Maharashtra’s total neonatal deaths ( Saunik et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Infant Mortality Rate (IMR) among tribal children surpasses the national average of India by 30% ( Dasra, 2016 ). Bhamaragadh’s neonatal mortality is high, accounting for 12.4% of Maharashtra’s total neonatal deaths ( Saunik et al, 2017 ). Furthermore, a child born into a tribal family has a 19% higher chance of dying in the neonatal period and 45% higher risk of dying in the post-neonatal period compared with children of other social groups ( Narain, 2019 ).…”
Section: Discussionmentioning
confidence: 99%